Covid-19 and nursing home residents: The potential role of geriatric nurses in a special crisis - Salman Barasteh; Amir Vahedian Azimi; Fatemeh Khademi; Salime Goharinezhad; Maryam Rassouli (Tehran University of Medical Sciences, 2020)
COVID-19 pandemic has led to serious challenges in nursing homes around the world. In addition to age-related conditions, living in nursing homes are more likely to be infected with COVID-19 due to the use of shared living space, gathering in common dining and recreational areas, and limited technical and human resources. Nurses play an important role in meeting the complex needs of the elderly in the crisis and it is essential to use specialist nurses for addressing the physical and psychological needs of this high-risk population. In this crisis, the lack of geriatric nurses in nursing homes in Iran causes problems such as the rapid spread of infection, lack of access to quarantine and proper prevention, and further infection of patients and caregivers. These specialist nurses could take many responsibilities in a special condition such as the provision of specialized courses for other care providers who are working in these facilities to prevent the complications of being affecting by the disease. Therefore, it is recommended to prioritize the employment of specialist geriatric nurses, support staff more, and use appropriate technologies to minimize contact with patients, effectively train volunteers in the programs of these centers. It also Necessary to formulate and implement strict regulations and guidelines by these nurses to prevent, rapid diagnosis, and infection control, personal protection, meeting, and isolation of residents of nursing homes.